2005
DOI: 10.1200/jco.2005.01.685
|View full text |Cite
|
Sign up to set email alerts
|

Results of the Dutch National Study of the Palliative Effect of Irradiation Using Two Different Treatment Schemes for Non–Small-Cell Lung Cancer

Abstract: The 10 x 3-Gy radiotherapy schedule is preferred over the 2 x 8-Gy schedule for palliative treatment, as it improves survival and results in a longer duration of the palliative response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
90
1
4

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(98 citation statements)
references
References 25 publications
3
90
1
4
Order By: Relevance
“…In contrast, a study conducted by the National Cancer Institute of Canada [13], found that patients treated with fractionated radiotherapy (20 Gy), had greater improvement in symptoms, ability to carry out normal activities, and better global quality of life than patients treated with single fraction of 10 Gy. Bezjak et al [13] and Erridge et al [15], reported better palliation with higher dose and more fractionated regimen.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, a study conducted by the National Cancer Institute of Canada [13], found that patients treated with fractionated radiotherapy (20 Gy), had greater improvement in symptoms, ability to carry out normal activities, and better global quality of life than patients treated with single fraction of 10 Gy. Bezjak et al [13] and Erridge et al [15], reported better palliation with higher dose and more fractionated regimen.…”
Section: Discussionmentioning
confidence: 99%
“…In the MRC 1996 [9], shorter regimen of 2 fractions, have more rapid onset of palliating symptoms than higher dose of 13 fractions, although the differences in the proportion of patients who were palliated were not significant. Kramer et al [15] showed that both regimens of 30 Gy/10 fractions and 16 Gy/ 2 fractions were effective in controlling symptoms, but the duration of palliative effect was significantly longer with 30 Gy / 10 fractions compared to 16 Gy/ 2 fractions. MRC 1991 [6], found that the median duration of palliation was similar in the two treatment groups; it ranged from 46 to 73 days in the two-fraction group and from 45 to 101 days in the single fraction group and palliation of symptoms last for at least 50% of survival time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[4] was drafted, and then updated [5] to determine the most effective and least toxic palliative radiotherapy regime to improve or prevent thoracic symptoms and/or overall survival. In this review, of 14 randomized control trials [6][7][8][9][10][11][12][13][14][15][16][17][18][19], the authors concluded that there was no strong evidence that any of the reviewed dose fractionation schedules provided greater palliation than the other. Patients with good performance status and treated with higher doses of radiotherapy had a modest increase in survival of 5 % at 1 year and 3 % at 2 years, but at the cost of increased acute toxicity, in particular esophagitis.…”
Section: External-beam Radiotherapymentioning
confidence: 99%
“…Fairchild et al [20] performed a meta-analysis of 3,473 patients from 13 randomized trials [6][7][8][9][10][11][12][13][15][16][17][18][19] since 1985 that evaluated different dose fractionation schemes for palliative lung radiotherapy. The authors found that there was a greater likelihood of symptom improvement and a modest benefit in overall survival with radiotherapy schedules of 35 Gy 10 BED (i.e., 30 Gy in ten fractions) or greater.…”
Section: External-beam Radiotherapymentioning
confidence: 99%